Infectious Disease and National Security Strategic Information Needs - Cecchine, Gary (RAND Corporation, 2006)
The pace of global travel, migration, and commerce has brought about an increased risk of a worldwide infectious disease outbreak. This report examines infectious disease within the context of national security and assesses the need for and adequacy of information that will enable U.S. policymakers to prevent and respond to such threats.